CHALLENGES OF ISLAMIC TEACHERS IN IMPLEMENTING THE TAHFIZ QURAN PROGRAM DURING THE COVID-19 PANDEMIC - Rasyid Anwar Dalimunthe; Ruslan Efendi; Masruroh Lubis (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this study was to determine the challenges and how to minimize the challenges in implementing the Quran tahfiz program at Al Azhar Private Primary School Medan. The method used by researchers is descriptive qualitative method and using interview and observation instruments and data analysis using triangulation. From the results of the research obtained, the challenges faced by the teacher were the large amount of time that was missed because students did not follow the Quran tahfiz program on time, intermittent communication due to network disturbances, the memorization given was incomplete, some students often forgot what they had memorized or deposited. Whereas the teachers way of minimizing these challenges, ustadz always reminded him via WhatsApp before the implementation of the Quran tahfiz program began, always asked students to memorize assignments before the deposit day, always reminded students via WhatsApp to repeat their memorization at home. As for the conclusion of this study, the importance of the cooperation of teachers and parents in paying attention, directing and motivating students to take part in the learning process, especially in following the implementation of the tahfiz Quran program from schools.Keywords: Various Challenges, Islamic Religion Teacher, Tahfiz Program, Covid-19